Molecular diagnosis and genetic counselling of fragile X syndrome - Özbey, Ülkü; Yüce, Hasan (My University, 2007)
The fragile X syndrome (FRXS) is the most frequent cause of inherited mental retardation. It is caused by the progressive expansion of (CGG)n trinucleotide repeats located in the promoter region of the (Fragile X mental retardation 1 gene) FMR1 gene at Xq27.3. The cloning of the FMR1 gene and the elucidation of the molecular basis of the FRXS is of great importance for the diagnosis and understanding of this unusual type of mutation. The mechanism behind the transition from stable normal (CGG)n alleles to the carrier state and from premutation to mutation is partially understood. The clinical diagnosis of fragile X mental retardation (FXMR) is not possible as dysmorphic features are subtle. Molecular diagnosis by Southern Blot is the confirmatory test that makes carrier detection. As the risk of recurrence of FXMR is high in the family and carrier relatives, an identification of fragile X positive children, and offering carrier detection and prenatal diagnosis to the families is very important. It is possible by screening mentally retarded children and adults even if there is no family history of mental retardation or typical behavioral or physical features associated with the fragile X phenotype. In this review, the courses that will be followed at appropiate socio-psychological approaches, clinical follow-up and diagnosis that includes genetic counselling period and the diagnostic methods for the families with FRXS are discussed based on the literature. The complexities due to premutation and the variable severity of manifestations in carrier females need to be understood while counseling fragile X families.
Frajil X sendromunun moleküler tanisi ve genetik danişmanlik
Keywords: article; chromosome Xq; diagnostic procedure; disease carrier; disease severity; fragile X syndrome; gene mutation; genetic counseling; human; mental deficiency; molecular cloning; prenatal diagnosis; recurrence risk; Southern blotting; trinucleotide repeat